Identification of nonlinear dynamic systems described by Hammerstein state-space models with discontinuous nonlinearities. (2017) - Salhi, Houda; Kamoun, Samira
This paper deals with the parameter estimation problem of Hammerstein state-space models with different nonlinearities. The basic idea is to develop a recursive algorithm which estimate jointly the system model parameters and the state variables by combining the adjustable model method, the least squares technique and the Kalman filter. A numerical example is provided to test the flexibility and the effectiveness of the proposed algorithm.